Study of associated gas components and combustion characteristics based on nitrogen-assisted steam stimulation of heavy oils. (15th December 2020) - Yan, Huiting; Liu, Zhenyi; Zhang, Jun; Xiao, Fengpu; Dong, Hai; Li, Mingzhi; Li, Pengliang; Fan, Tao
Highlights: Heavy oils experiments of nitrogen-assisted steam stimulation at different conditions. Combustion experiments at the temperature of 40–120 °C and the pressure of 1–15 MPa. Effects of diverse conditions on components of associated gas. Flammability limit range widened (1.02% to 60.05%) by pressure or temperature rise. Lowest limiting oxygen concentration reached 8.2% in experiments. Abstract: Nitrogen-assisted steam stimulation (NASS) technology is a widely used heavy oil extraction technology. Most previous studies on the NASS of heavy oil focused on recovery improvements. To study the safety of the associated gas generated during the NASS process of heavy oil, a series of simulation experiments was performed on oil samples from a heavy oil reservoir. The results showed that the effect of pressure and temperature on the components of the associated gas can be ignored during the nitrogen injection. In the process of steam injection, the higher the oxygen content in the injected gas is, the greater the amount of produced combustible gas becomes, which is dangerous. Experiments on the associated gas flammability were conducted to study the effects of temperature (40–120 °C) and pressure (1–15 MPa) on the upper flammability limit (UFL), lower flammability limit (LFL) and limiting oxygen concentration (LOC). The results showed that an increase in the initial pressure or temperature led to a wider flammability limit range, and the LOC decreased. During the tests, the explosive limit of the flammable mixture ranged from 1.02% to 60.05%, and the lowest LOC was 8.2%. These results are meaningful for safety control in heavy oil development.